Interpretasi Ekosistem Ekonomi Digital Bagi Pelaku Usaha Mikro Perempuan - Yuni Ekawarti; Esti Tri Endarwati (UNIVED Press, 2022)
MSME entrepreneurs in Indonesia are mostly managed by women from their homes, these women are able to show their fangs in the business world even though they are still at the level of MSME scale. However, the obstacles many women face is that still many of them who are lack of knowledge about managing their business finances digitally, most of them only do simple recording manually. The purpose of this study is to find out whether digital business financial management has been used and utilized optimally by MSMEs, especially those owned by women in Palembang City. The data obtained from this study by distributing a questionnaire where there are 73 respondents of female MSME entrepreneurs in Palembang City. The data analysis techniques used multiple linear regression with the help of SPSS 20 for Windows. The results of the research obtained are Human Resources of Entrepreneurs, Artificial Resources of MSME Entrepreneurs, Natural Resources affecting the readiness of technological literacy of female MSME entrepreneurs in Palembang City with a coefficient of determination of 0.643.